SavingLife: An Educational Technology for Basic and Advanced Cardiovascular Life Support - Najma Naz; Ali Sayyed; Grace Teresinha Marcon Dal Sasso; Sabiha Khanum; Maria de Lourdes de Souza (MDPI AG, 2018)
The development of information and communication technologies and the accessibility of mobile devices has increased the possibilities of the teaching and learning process anywhere and anytime. Mobile and web application allows the production of constructive teaching and learning models in various educational settings, showing the potential for active learning in health. The objective of this study was to present the design and development of an educational technology (SavingLife, a web, and mobile-based application) for learning cardiopulmonary resuscitation and advanced cardiovascular life support for adults. SavingLife is a technological production, based on the concept of virtual learning and problem-based learning approaches. SavingLife was developed using five phases (analyze, design, develop, implement, evaluate) of the instructional systems development process. The technology presents 10 scenarios and 12 simulations, covering different aspects of basic and advanced cardiac life support skills. The contents can be accessed in a non-linear way leaving the students free to build their knowledge based on their previous experience. Each scenario is presented through interactive tools such as scenario description, assessment, diagnose, intervention and re-evaluation. Animated ECG rhythms, text documents, images, and videos are provided to support procedural and active learning considering the real-life situations. Accessible equally on small to large devices with or without an internet connection, SavingLife offers a dynamic, interactive and flexible tool, placing students at the center of the learning process. SavingLife can contribute to the student’s learning in the assessment and management of basic and advanced cardiac life support for adults, in a safe and ethical way.